ASSESSMENT OF FUEL PROPERTIES OF BIODIESEL FUEL FROM WASTE OIL - M.MATHIYAZHAGAN; S.SENTHILNATHAN; A.ARJUNAN; M.MUTHUSELVAM; A.GANAPATHI (International Journal of Pharma and Bio Sciences, 2012)
The main aim of this study is to reduce the use of petroleum diesel by using domestic renewable sources such as waste oil as fuel. Ever increasing of diesel engine usage due to its higher fuel efficiency can cause severe environmental damage particularly urban areas. Rapid growth of population, urbanization and industrialization are the main factors which increase the air pollutants particularly CO2 emission to the environment. Continuous addition of CO2 emission to atmosphere is responsible for the formation of global warming, acid rain and cancer risks etc. Biodiesel is the primary source to solve the entire above problems. Because it is a renewable, low polluted, non-toxic, biodegradable well known alternative fuel to diesel engines. Presently most of the biodiesel fuels are produced from food grade oils only. Biodiesel from food oils can cause food oil crisis and increases the production cost of biodiesel. This will encourage the development of biodiesel from cheapest sources like non-edible oils and waste oils. Therefore present investigation was made to produce biodiesel fuel from waste oil and the important fuel properties were analyzed.